Optimalisasi Branding Melalui Digitalisasi Bisnis UMKM Dapoer Athakiela - Ruthyanti Manihuruk; Gendut Sukarno (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The community service program aims to improve branding capabilities in Micro, Small and Medium Enterprises (MSMEs). In the digital era, MSMEs face big challenges in marketing their products effectively. For this reason, this program is designed to provide comprehensive training and assistance in building a strong brand and an effective digital marketing strategy. Athakiela Kitchen, as one of the MSMEs in Wiyung District, has not yet carried out branding for its business. The focus of this service is to help Kitchen Athakiela MSMEs implement good branding using digital marketing. The service method used is through counseling and training on branding and digital marketing. The results obtained from this service were the creation of the Athakiela Kitchen branding by creating an MSME logo, product labels, banners and product photos. Athakiela Kitchen can also market its products through the Instagram account that has been created.